2021
DOI: 10.1039/d1py00116g
|View full text |Cite
|
Sign up to set email alerts
|

Composition processing property relationship of vitrimers Based on polyethyleneimine

Abstract: The composition-processing-properties relationship of imine containing reversible covalent bonds containing polymers (RCBPs) was studied using an innovative (regarding this type of polymers) combination of characterization methods. This combination led, for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…This is attributed to the change in the chemical structure of the PIs with higher temperature and/or compression times. As discussed earlier, 52 during heating, imine bonds reduce to amines. Thus, the higher the temperature (above 175–180°C), the lower the number of imine bonds.…”
Section: Resultsmentioning
confidence: 61%
See 4 more Smart Citations
“…This is attributed to the change in the chemical structure of the PIs with higher temperature and/or compression times. As discussed earlier, 52 during heating, imine bonds reduce to amines. Thus, the higher the temperature (above 175–180°C), the lower the number of imine bonds.…”
Section: Resultsmentioning
confidence: 61%
“…Previous work 52 indicated that crosslink density increases with compression molding time, until it levels off after 20 min. Crosslink density follows PI < PI‐10 < PI‐20 ≅ PI‐40 ≅ PI‐60 , along with an increase in vitrification temperature or topology freezing transition temperature ( T v ) from 86°C to 135°C.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations